36=-40-2x

Simple and best practice solution for 36=-40-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 36=-40-2x equation:


Simplifying
36 = -40 + -2x

Solving
36 = -40 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
36 + 2x = -40 + -2x + 2x

Combine like terms: -2x + 2x = 0
36 + 2x = -40 + 0
36 + 2x = -40

Add '-36' to each side of the equation.
36 + -36 + 2x = -40 + -36

Combine like terms: 36 + -36 = 0
0 + 2x = -40 + -36
2x = -40 + -36

Combine like terms: -40 + -36 = -76
2x = -76

Divide each side by '2'.
x = -38

Simplifying
x = -38

See similar equations:

| f(-2x)=1.5x+12 | | f(x)=x^4+3x^3-21x^2-33x+110 | | 11/2•3 | | 2x+8-2x-8=0 | | y^2-2y-8x-7=0 | | F(2)=9x-5 | | -3-25a=15 | | 9(3z-1)=18z+45 | | 9(3z-1)=18z+45 | | 7/8*1/4 | | 2x^2+2y^2-12x+9=0 | | 16/5=x-12/25 | | -20-(4x-1)=-51 | | -3/5(7-4x)=25 | | 6x-12=9x-15 | | Xy(2y-3x)= | | -2y-10+2x=o | | gn=3*(-2)n-1 | | 2((5x^2)+8x-3)=0 | | -4x-(-5)/-7=13 | | 6x+3x+5=-7x+4-2 | | an=7+.2(n-1) | | 3v+1=4-4(2v-2) | | 1/5(3r-4)=3d | | 6/21-5/7 | | x^2-5x+-36=0 | | 4(3r-2)=(r+7) | | an=7+2(n-1) | | 5a+3-10a=3a+27 | | -2/-3x=20 | | 1/2x-1/2=3/4 | | -5.5x+-0.56=-1.64 |

Equations solver categories